CHARACTERIZATION OF THE α-AMYLASE GENE FROM Bacillus sp. BBM1 - MUÑOZ, Juliana; QUINTERO, Mónica; GUTIÉRREZ, Pablo A. (Vitae, 2011)
Starch degrading enzymes represent about 30% of the enzyme world and they are used in the production of glucose, maltose and oligosaccharides, which can be further processed to produce fructose and dextrose syrups. The resulting glucose can also be fermented for the production of ethanol, amino acids and organic acids. α-amylases are also used as an alternative to the addition of malt in the beer industry, the improvement of flour in the baking industry, the removal of starch in the paper and textile industry, and as a detergent additive. In this paper, the complete nucleotide sequence of the α-amylases BBM1 produced by the native strain Bacillus sp. BBM1 is reported. The deduced aminoacid sequence shows that this enzyme is translated as a 659 a.a. protein, which after the secretion cleaves to generate a 618 mature enzyme of 68 kDa. The BBM1 α-amylases is transcribed as a monocistronic mRNA, as it is suggested by the presence of inverted repeat elements upstream and downstream of the protein coding region. The expression of the BBM1 α-amylase is under the control of the AmyR1 allele from the AmyO operator sequence, which is recognized by the regulatory protein CcpA. In contrast to most α-amylases, BBM1 seems to possess two additional carbohydrate-binding domains, which probably increase its efficiency in the degradation of granular starch. A homology model of the enzyme is presented and its interaction with calcium ions and substrate is analyzed.